Foreword - Rowe, William (Management and Leadership in Social Work: A Competency-Based Approach, 2020)
WOS:000486506700001
Keywords: dept.swk; ⛔ No DOI found

COVID-19 and Youth in Detention - Rowe, William (Child & Youth Services, 2020)
2 citations (Crossref) [2023-10-31] WOS:000605582700034
Keywords: dept.swk; peer-reviewed

Supervised injection sites: Harm reduction and health promotion - Rowe, William S.; Rapp, Lisa (Responding to the oppression of addiction: canadian social work perspectives, 2017)
Keywords: dept.swk; ⛔ No DOI found

Responding to the oppression of addiction: Canadian social work perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2017)
Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; therapy; Social Work; Canada

Responding to the Oppression of Addiction: Canadian Social Work Perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2010)
"Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community."–pub. desc.
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; faculty_collection; therapy; Social Work; Canada

Client-centered theory and the person centered approach: Values-based, evidence-supported - Rowe, William S. (Social work treatment: Interlocking theoretical approaches, 2017)
Keywords: dept.swk